THE EFFECT OF AUGMENTED REALITY MEDIA ON IPAS LEARNING OUTCOMES REGARDING THE HUMAN RESPIRATORY SYSTEM OF FIFTH-GRADE STUDENTS AT SDN PAKIS V SURABAYA - Arimbi Salma Bahira; Savitri Suryandari; Anna Roosyanti (SOSIOEDUKASI, 2026)
This study aims to determine the effect of Augmented Reality learning media on IPAS learning outcomes in human respiratory system material for fifth grade students at SDN Pakis V Surabaya. This research used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 70 students, including 35 students from class 5C as the experimental class and 35 students from class 5B as the control class. The sampling technique used was purposive sampling. Data were collected through tests in the form of pretest and posttest. The data were analyzed using normality test, homogeneity test, and paired samples t-test with the assistance of IBM SPSS Statistics 21. The results showed that the average score of the experimental class increased from 54 in the pretest to 79 in the posttest, with an increase of 25 points. Meanwhile, the average score of the control class increased from 52 in the pretest to 64 in the posttest, with an increase of 12 points. The paired samples t-test result in the experimental class showed a significance value of 0.000 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that Augmented Reality learning media has an effect on IPAS learning outcomes in human respiratory system material for fifth grade students at SDN Pakis V Surabaya